BAGAIMANA PENERAPAN GREEN HUMAN RESOURCES MANAGEMENT DITERAPKAN? SEBUAH ANALISIS BIBLIOMETRIK - Judijanto, Loso (Gapenas Publisher, 2025)
This study aims to map the development and trends in research in the field of Green Human Resource Management (Green HRM) using a bibliometric approach. Using data from the Scopus database and analyzed using VOSviewer software, this study explores keyword emergence patterns, author and institutional collaboration networks, and inter-country contributions to the development of Green HRM literature. The visualization results show that the most dominant themes are sustainability, environmental management, and green behavior, which are closely related to the concepts of employee engagement, corporate social responsibility, and transformational leadership. Malaysia, Pakistan, and China are noted as the countries with the most prominent research contributions, supported by strong and productive institutional networks. In addition, temporal trends and keyword density indicate a shift in research focus towards the practical implementation of Green HRM in an organizational context. This study provides a theoretical contribution by expanding the conceptual understanding of Green HRM and offers practical implications for organizations to design sustainable HR strategies. However, the limitations of using a single database and a purely quantitative approach open up opportunities for further research using qualitative or mixed-method approaches.